POWERS OF THE PRESIDENT OF ROMANIA IN RELATIONSHIP WITH GOVERNMENT - Oana ŞARAMET (AGORA International Journal of Juridical Sciences No. 1 (2016), pp. 23-28, 2016)
According to constitutional provisions in force, Romania has a dualist executive whose central authorities are the President of Romania and the Government. Consecrating a semi-presidential regime, the constitutional legislator has built such an executive so the relations between the president and the government have to be characterized by cooperation, collaboration, including those between the President and Prime Minister. Thus, our Constitution recognizes to the President the powers regarding the procedure of investiture of a new government, the appointment and dismissal of some government members, the President also having the possibility to consult with the government and to participate in its meetings.
Keywords: powers; President; collaboration; Government; designation; dismissal; Prime Minister